2016
DOI: 10.4269/ajtmh.16-0088
|View full text |Cite
|
Sign up to set email alerts
|

Scrub Typhus in Northeastern Thailand: Eschar Distribution, Abnormal Electrocardiographic Findings, and Predictors of Fatal Outcome

Abstract: Abstract. Scrub typhus is endemic in Thailand. Of the 495 patients with acute undifferentiated fever studied in Maharat Nakhon Ratchasima Hospital, Nakhon Ratchasima, Thailand, from June 1, 2011, to December 31, 2012, 146 patients (29.5%) had confirmed scrub typhus. The majority of cases were male, farmers, with the mean (±standard deviation) age of 54.1 ± 15.2 years. A total of 59 patients (40.4%) had eschar lesion. The commonest sites for an eschar in male patients were the perineum, inguinal, and buttock ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
28
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
7
28
2
Order By: Relevance
“…In another Thailand study, abnormal ECG was found in 39 of 79 patients (49.4%), including sinus tachycardia (17 patients, 21.5%), new onset AFib (nine patients, 11.3%). 8 In a Papua New Guinea study conducted in 1945, no significant ECG changes were observed in patients with scrub typhus 9 ; a study conducted in Thailand in 2002 revealed that mild ECG changes (e.g., ST-T change, U wave, VPB) were observed in only 24% of patients. 10 However, in this study, ECG abnormalities were observed in 72 (43.6%) of 165 scrub typhus patients and this result is higher than previous report by Kim et al, 11 where ECG abnormalities were observed in about one-third of scrub typhus patients.…”
Section: Discussionmentioning
confidence: 98%
“…In another Thailand study, abnormal ECG was found in 39 of 79 patients (49.4%), including sinus tachycardia (17 patients, 21.5%), new onset AFib (nine patients, 11.3%). 8 In a Papua New Guinea study conducted in 1945, no significant ECG changes were observed in patients with scrub typhus 9 ; a study conducted in Thailand in 2002 revealed that mild ECG changes (e.g., ST-T change, U wave, VPB) were observed in only 24% of patients. 10 However, in this study, ECG abnormalities were observed in 72 (43.6%) of 165 scrub typhus patients and this result is higher than previous report by Kim et al, 11 where ECG abnormalities were observed in about one-third of scrub typhus patients.…”
Section: Discussionmentioning
confidence: 98%
“…Most patients in our study presented with nonspecific symptoms such as fever (91%), exanthema (55%), and headache (45%). Prevalence of the characteristic eschar in scrub typhus patients can vary greatly [13][14][15] and might depend on the O. tsutsugamushi genotype. 16 In our study, nearly half of the patients presented with an eschar.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterium is passed on via Trombiculidae mites (chiggers); 1–2 days after a chigger bite, an erythematous papule develops at the bite site and gradually turns into a painless eschar lesion . There is a difference in predominant sites of eschar between men (the perineal, inguinal and buttock areas) and women (trunk, especially front above the umbilicus) . Multiple eschars can be seen in some patients.…”
mentioning
confidence: 99%
“…Despite the absence of eschar lesion, rickettsial infection was strongly suspected, as Thailand, especially Chiang-Mai, is known to be an endemic area for scrub typhus. 1 Consequently, azithromycin for empirical treatment of scrub typhus and Mycoplasma pneumonia was initiated while serological diagnosis was awaited. The following day (day 7 of the illness), tests for M. pneumoniae antibodies came back negative.…”
mentioning
confidence: 99%
See 1 more Smart Citation